N‐terminal pro‐brain natriuretic peptide in the assessment of respiratory distress in term neonates. Issue 3 (10th March 2014) - Markovic‐Sovtic, Gordana; Kosutic, Jovan; Jankovic, Borisav; Bojanin, Dragana; Sovtic, Aleksandar; Radojicic, Zoran; Rakonjac, M. Zorica
Abstract Background N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) is used as a biomarker to differentiate congestive heart failure from lung disease in adults and children. The clinical significance of its use in term neonates has not yet been extensively studied. Methods NT‐proBNP level was measured in 62 term neonates admitted for respiratory distress (RD): 38 with congenital heart disease (CHD) and 24 with pulmonary disease. The control group consisted of 28 healthy neonates. Findings of auscultation, chest radiography, Silverman–Anderson score and echocardiography were recorded for each patient. Blood samples for measuring NT‐proBNP were collected on admission, when blood sampling was indicated for the clinical management of the newborn. Results In the control group NT‐proBNP was significantly higher during the first week of life compared to the rest of the neonatal period (P < 0.001). The RD group, regardless of etiology, had significantly higher NT‐proBNP than the control group (P < 0.001). Neonates with more severe RD had significantly higher NT‐proBNP (P = 0.002). No significant difference was found between the RD group with CHD and those with pulmonary disease. Neonates with CHD and myocardial hypocontractility had significantly higher NT‐proBNP than those with normal contractility (P = 0.022). Conclusion Term neonates with RD have significantly higher NT‐proBNP than healthy neonates. A single measurement of NT‐proBNP level cannot be used as the sole biomarker for distinguishing between cardiac and pulmonary cause of RD in term neonates.